(untitled) (Journal of the Spanish Institute for Strategic Studies, 2024)
The Ukrainian war has awakened old fears in Europe. This war has its origins in ethno-cultural issues that go back centuries. To understand the origin of the conflict between Russians and Ukrainians, it is necessary to go back to the Russian empire, which is reflected today in aspects such as language and religion. In such a conflict, cultural property becomes a potential victim and subject to manipulation, plunder, damage and destruction. Since the beginning of the war, hundreds of cultural properties in Ukraine have been damaged or destroyed despite international regulations protecting heritage in the event of armed conflict, much of which has been ratified by both Kiev and Moscow. This paper will begin by analyzing Ukrainian versus Russian national identity from its origins to the present day, continue by examining the mechanisms of protection of cultural property applicable to this case, as well as the damage suffered to this day by Ukrainian heritage, and try to determine whether such acts are contrary to international law and how they can they be judged.